Influence of Corporate Characteristics on Firm Leverage: Evidence from Bangladesh - Hossain, S. M Khaled; Akib, Jobaer Hossan; Rahman, Md Matiur (Journal of Empirical Studies, 2020)
The purpose of the paper is to explore the influence of various corporate characteristics on financial leverage of the manufacturing companies listed at Dhaka Stock Exchange (DSE) in Bangladesh. A non-probability sampling technique has been used for selecting sample size from the population. Data from 40 manufacturing companies has been analyzed from 2015 to 2019-time period which are secondary in nature. Multiple regression methods were implied to explore the impact of corporate characteristics on leverage of the studied firms. The output from the regression models indicated that total assets, return on assets, return on sales and age are inversely and significantly connected to the leverage of companies. Selecting only the manufacturing company as the sample is a little limitation for this study. The study period is only five years including year of 2015-2019. The research results of this paper make contributions for the regulatory and enforcement authorities such as: ICAB, ICMAB, SEC and DSE. The information derived from the findings of the study will help financial managers to take decision regarding selection of optimal capital structure.